Nanozyme Based on Porphyrinic Metal–Organic Framework for Electrocatalytic CO2 Reduction. Issue 1 (13th October 2022) - Lee, Junghye; Choi, Hansaem; Mun, Jinhong; Jin, Eunji; Lee, Soochan; Nam, Joohan; Umer, Muhammad; Cho, Jaeheung; Lee, Geunsik; Kwon, Youngkook; Choe, Wonyoung
Abstract : Mimicry of natural enzyme systems is an important approach for catalyst design. To create an enzyme‐inspired catalyst, it is essential to mimic both the active center and the second coordination sphere. Metal–organic frameworks (MOFs), an emerging class of porous materials, are ideal candidates for heterogeneous catalysts because their versatile building blocks confer a high level of structural tunability, and the chemical environment surrounding the active center can be controlled at the molecular level. Herein, a new 2D porphyrinic MOF, PPF‐100, constructed from a nonplanar saddle‐distorted porphyrin linker and a Cu paddle‐wheel metal node is reported. The strategic introduction of ethyl substituents allows not only to mimic the active center and second coordination sphere but also to increase the catalytic selectivity while completely inhibiting H2 generation in the CO2 reduction reaction. Abstract : A new 2D porphyrin‐based metal–organic framework (MOF) is constructed from a highly nonplanar saddle‐distorted porphyrin linker to mimic natural enzymes. This MOF exhibits remarkable hydrophobicity and outstanding water and chemical stability. Furthermore, the prepared MOF nanozyme shows a significant hydrophobic surface and displays excellent catalytic selectivity and performance for the electrochemical conversion of CO2 to CO.